2017
DOI: 10.1002/hep.28964
|View full text |Cite|
|
Sign up to set email alerts
|

Prohibitin 1 suppresses liver cancer tumorigenesis in mice and human hepatocellular and cholangiocarcinoma cells

Abstract: Prohibitin 1 (PHB1) is best known as a mitochondrial chaperone and its role in cancer is conflicting. Mice lacking methionine adenosyltransferase α 1 (MATα1) have lower PHB1 expression and we reported c-MYC interacts directly with both proteins. Furthermore, c-MYC and MATα1 expert opposing effects on liver cancer growth, prompting us to examine the interplay between PHB1, MATα1 and c-MYC and PHB1's role in liver tumorigenesis. We found PHB1 is highly expressed in normal hepatocytes and bile duct epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 30 publications
1
78
0
Order By: Relevance
“…More recently, our study and others have shown that MATα1 can target the nuclear compartment where it can regulate gene expression by epigenetic mechanisms . In addition, we recently showed that MATα1 interacts directly with MAX and c‐MYC and negatively regulates E‐box‐driven reporter activity . This prompted us to investigate the MATα1 interactome, which revealed the unexpected high number of mitochondrial proteins, including CYP2E1 (Supporting Table ).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…More recently, our study and others have shown that MATα1 can target the nuclear compartment where it can regulate gene expression by epigenetic mechanisms . In addition, we recently showed that MATα1 interacts directly with MAX and c‐MYC and negatively regulates E‐box‐driven reporter activity . This prompted us to investigate the MATα1 interactome, which revealed the unexpected high number of mitochondrial proteins, including CYP2E1 (Supporting Table ).…”
Section: Discussionmentioning
confidence: 75%
“…(26)(27)(28) In addition, we recently showed that MATα1 interacts directly with MAX and c-MYC and negatively regulates E-box-driven reporter activity. (19) This prompted us to investigate the MATα1 interactome, which revealed the unexpected high number of mitochondrial proteins, FIg. 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group reported that hepatic PHB1 expression is reduced during chronic cholestatic injury in both experimental murine models and in humans (10,11). We also reported that liverspecific Phb1 knockout mice develop hepatocellular carcinoma (HCC) 3 (12) and that Phb1 heterozygotes are predisposed to cholestasis-associated cholangiocarcinoma (CCA) (13). We found that hepatic PHB1 expression is down-regulated at the mRNA level in the majority of human patients with HCC and CCA, and reduced PHB1 expression increases the growth of HCC and CCA cells and inversely correlates with tumor growth in the murine CCA model (13).…”
Section: To Understand the Molecular Basis For These Observations Wementioning
confidence: 86%